Conceptualizing and measuring state regulation of reproductive processes: The international reproduction policy database - Hannah Zagel; Rohan Khan; Anna E. Kluge; Mio Tamakoshi; Martin Gädecke (Journal of European Social Policy, 2024)
This article critically reviews existing concepts and measurements of how states regulate reproductive processes such as contraceptive use, abortion and pregnancy, and introduces a new conceptually-grounded international policy database on reproduction policies. With regulating reproduction, states get involved in whether, when and how people enter or avert, carry out or end pregnancy and procreation; and who is supported in their reproductive pathways in the first place. Building on comparative welfare state scholarship, we suggest that state regulation of reproduction is best understood multi-dimensionally, distinguishing regulatory levels, regulatory types, permissiveness, in-kind generosity, and in-cash generosity. Not least due to a lack of data, previous research has mostly been limited to case studies or to individual policy fields, such as abortion policy. This review summarizes the state of comparative perspectives in this policy domain, and presents the International Reproduction Policy Database (IRPD), which proposes a novel and comprehensive way to measure and compare reproduction policies. IRPD covers the regulative structure, permissiveness, and generosity of state-provided reproduction policies in 33 middle- and high-income countries from 1980 to 2020, across five policy fields: sex education, contraception, abortion, medically assisted reproduction and pregnancy care. The review closes with an empirical example from the new database and gives an outlook on its research potentials.
Keywords: 320; reproduction policy; policy data; reproductive rights; permissiveness; generosity; abortion